Exosome in renal cell carcinoma progression and implications for targeted therapy - Li, Xinwei; Xiao, Wen; Yang, Hongmei; Zhang, Xiaoping (Frontiers in Oncology, 2024)
Renal cell carcinoma is a urological malignancy with a high metastatic rate, while targeted therapy for renal cell carcinoma still has much room for improvement. Some cutting-edge researches have focused on exosome in cancer treatment and there are some breakthroughs in breast cancer, lung cancer, and pancreatic cancer. Up to now, exosome in renal cell carcinoma progression and implications for targeted therapy has been under research by scientists. In this review, we have summarized the structure, formation, uptake, functions, and detection of exosomes, classified the mechanisms of exosomes that cause renal cell carcinoma progression, and listed the promising utilization of exosomes in targeted therapy for renal cell carcinoma. In all, based on the mechanisms of exosomes causing renal cell carcinoma progression and borrowing the successful experience from renal cell carcinoma models and other cancers, exosomes will possibly be a promising target for therapy in renal cell carcinoma in the foreseeable future.